Portfolio diet and LDL-C in a young, multiethnic cohort: cross-sectional analyses with cumulative exposure modeling - Victoria Chen; Laura Chiavaroli; Andrea J. Glenn; Meaghan E. Kavanagh; Tara Zeitoun; Sara Mahdavi; Cyril W. C. Kendall; David J. A. Jenkins; Ahmed El-Sohemy; John L. Sievenpiper (BMC Public Health)
Abstract Background The Portfolio Diet is a plant-based dietary pattern of cholesterol-lowering foods that has demonstrated clinically meaningful reductions in low-density lipoprotein cholesterol (LDL-C) and other cardiovascular risk factors. However, the Portfolio Diet has not been assessed in an ethnoculturally diverse population of young adults. Objective To examine the association of the Portfolio Diet Score (PDS) with LDL-C and other established cardiovascular risk factors in a young adult population. Methods This cross-sectional analysis included 1,507 men and women (mean age, 23 ± 3 years) of diverse ethnocultural backgrounds from the Toronto Nutrigenomics and Health Study. Diet was assessed by a validated Toronto-modified Harvard 196-item food frequency questionnaire with adherence to the Portfolio Diet measured using the Portfolio Diet Score. Data were analyzed using multiple linear regressions with adjustment for potential confounders. Modeling analyses related LDL-C levels according to absolute adherence to the Portfolio Diet with cumulative LDL-C and onset of rising cardiovascular risk by age. Results Participants were Caucasian (49%), East Asian (34%), South Asian (11%), or other (7%) with a mean LDL-C of 2.3 ± 0.7mmol/L. A 1-point higher PDS and higher PDS tertiles were associated with lower LDL-C (ß [95% CI] per 1-point: -0.009mmol/L [-0.016, -0.002], P = 0.013; Ptrend across tertiles =0.040), non-HDL-C (-0.010mmol/L [-0.018, -0.002], P = 0.014; Ptrend=0.028), total cholesterol (-0.011mmol/L [-0.019, -0.003], P = 0.011; Ptrend=0.038), systolic blood pressure (-0.150mmHg [-0.250, -0.050], P = 0.003; Ptrend<0.001) and diastolic blood pressure (-0.133mmHg [-0.219, -0.046], P = 0.003; Ptrend<0.001). Higher PDS tertiles were associated with lower triglycerides (Ptrend=0.039). A 1-point higher PDS was also associated with lower BMI (-0.038 kg/m2 [-0.071, -0.004], P = 0.026), waist circumference (-0.092cm [-0.171, -0.013], P = 0.022), body weight (-0.124 kg [-0.229, -0.019], P = 0.021) and FMI (-0.019 kg/m2 [-0.037, -0.001], P =0.039). There was no association with HDL-C, CRP, or fasting glucose. Modeling analyses suggest that compared to low adherence, 50% and 100% adherence to the Portfolio Diet may delay the onset of rising cardiovascular risk by an estimated 6 and 13 years, respectively. Conclusions Among young adults, the PDS was inversely associated with LDL-C and several other established cardiovascular risk factors. Early adherence to the Portfolio Diet may limit lifetime exposure to LDL-C and could delay the age at which cardiovascular events begin.